Parental loss of family members within two years of offspring birth predicts elevated absorption scores in college. Issue 5 (2nd September 2016) - Bahm, Naomi I. Gribneau; Duschinsky, Robbie; Hesse, Erik
ABSTRACT: Liotti proposed that interactions during infancy with a parent suffering unresolved loss could lead to vulnerabilities to altered states of consciousness. Hesse and van IJzendoorn provided initial support for Liotti's hypothesis, finding elevated scores on Tellegen's Absorption Scale - a normative form of dissociation - for undergraduates reporting that their parents had experienced the loss of family members within two years of their birth. Here, we replicated the above findings in a large undergraduate sample ( N = 927). Additionally, we investigated mother's and father's losses separately. Perinatal losses, including miscarriage, were also considered. Participants reporting that the mother or both parents had experienced loss within two years of their birth scored significantly higher on absorption than those reporting only perinatal, only father, or no losses. While not applicable to the assessment of individuals, the brief loss questionnaire utilized here could provide a useful addition to selected large-scale studies.